Management of Character Education Based on Local Wisdom - Endun Abdul Haq; Iim Wasliman; R. Supyan Sauri; Faiz Karim Fatkhullah; Ahmad Khori (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to identify and analyze: (1). Planning, (2).Organizing (3).Implementation (4). Evaluation. This research uses a qualitative approach with a case study method. Data collection is carried out by triangulation techniques using interviews, document studies, and field observations. Research location Baiturahman and MA Albasyariah Integrated High School Bandung. With the subject of the principal's research, teachers. The head of the Pencak silat hermitage, Data analysis was carried out through data reduction, data presentation, and conclusion drawing. Four important foundations are used in this research, including theological, philosophical, six value systems, and theoretical foundations. Then the theory that underlies this research is management theory and character theory. The findings of this study are (1). Planning for Character Education Based on Local Wisdom in the Development of Akhlakul Karimah for integrated high school students has been well structured and systematic, but the planning has not been oriented to the vision and mission of the school (2). The organization has been running according to the program with the same principle of understanding, commitment to responsibility even though it has not been supported by an adequate job analysis. (3). The implementation has gone well. However, they have not paid attention to the resources they have. (4). Evaluation according to the school's work program going forward, however, has not been followed up with innovative programs that meet the needs.